2011
DOI: 10.1007/s11136-011-9915-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EQ-5D in a general population sample in urban China

Abstract: The Chinese version of the EQ-5D demonstrated acceptable construct validity and fair to moderate levels of test-retest reliability in an urban general population in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 29 publications
11
106
0
Order By: Relevance
“…Second, the EQ-5D is constrained by significant ceiling effects in measuring HRQOL in the general population. 27,29 We also found a high prevalence of good sleep quality in our sample, which is supported by prior studies in mainland China. 23,33 This can be explained by reports suggesting that most generally healthy older adults experience satisfactory …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Second, the EQ-5D is constrained by significant ceiling effects in measuring HRQOL in the general population. 27,29 We also found a high prevalence of good sleep quality in our sample, which is supported by prior studies in mainland China. 23,33 This can be explained by reports suggesting that most generally healthy older adults experience satisfactory …”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies in mainland China. [27][28][29][30] Two facts may account for this finding. First, the survey participants lived a normal life at home, which implies better HRQOL than those who live in medical institutions for professional care.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, because this analysis was conducted on a cohort of Chinese patients from a larger patient population of East Asian patients (that included patients from mainland China, Hong Kong, Korea, Malaysia, Singapore and Taiwan), and there is no Chinese EQ-5D tariff, the commonly used UK tariff was used to calculate the utility scores (Brooks et al 2003). While there is evidence that different populations (including different racial/ethnic groups) value health states differently (Escobar et al 1983;Johnson et al 2005;Fu and Kattan 2006;Norman et al 2009), the EQ-5D has been shown to be useful for assessing QoL in patients with MDD (Sapin et al 2004) and to have acceptable validity and reliability in Asian populations (Wang et al 2012). In addition, both EQ-VAS and EQ-5D utility scores have been shown to be responsive to change in patients with depression (Günther et al 2008;Gerhards et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed to capture information on the consumption of major nutrients as well as specific Chinese foods, such as soy foods, fermented foods, salted foods, allium-type vegetables, and leafy vegetables; (4) the Zung Self-Rating Anxiety Scale (ZSAS) [9] and the Center for Epidemiologic Studies Depression Scale (CESD) [10] were used to determine mood for each subject. Anxiety and depression were present if ZSAS >44 and CESD ≥16; (5) the Pittsburgh Sleep Quality Index (PSQI) was used to measure the sleep quality of the participants [11]; (6) the EQ-5D was used to measure the health outcome of the participants [12]; (7) items from the Lawton and Brody Activity of Daily Living (ADL) scale-16 were used to elicit physical self-maintenance and instrumental activities of daily living, such as eating, using the telephone, preparing meals, handling money, and completing chores. Participants were considered to be functionally intact if the ADL score was over 16 [13].…”
Section: Methodsmentioning
confidence: 99%